X-ray detection of warm ionized matter in the Galactic halo. Issue 1 (23rd January 2016) - Nicastro, F.; Senatore, F.; Gupta, A.; Guainazzi, M.; Mathur, S.; Krongold, Y.; Elvis, M.; Piro, L.
Abstract: We report on a systematic investigation of the cold and mildly ionized gaseous baryonic metal components of our Galaxy, through the analysis of high-resolution Chandra and XMM–Newton spectra of two samples of Galactic and extragalactic sources. The comparison between lines of sight towards sources located in the disc of our Galaxy and extragalactic sources allows us for the first time to clearly distinguish between gaseous metal components in the disc and halo of our Galaxy. We find that a warm ionized metal medium (WIMM) permeates a large volume above and below the Galaxy's disc, perhaps up to the circum-galactic space. This halo WIMM imprints virtually the totality of the O i and O ii absorption seen in the spectra of our extragalactic targets, has a temperature of T _WIMM^Halo=2900 ± 900 K, a density n_H_WIMM^Halo = 0.023 ± 0.009 cm −3 and a metallicity Z_WIMM^Halo = (0.4 ± 0.1) Z⊙ . Consistently with previous works, we also confirm that the disc of the Galaxy contains at least two distinct gaseous metal components, one cold and neutral (the CNMM: cold neutral metal medium) and one warm and mildly ionized, with the same temperature of the halo WIMM, but higher density (n_H_WIMM^Disc = 0.09 ± 0.03 cm −3 ) and metallicity (Z_WIMM^Disc = 0.8 ± 0.1 Z⊙ ). By adopting a simple disc+sphere geometry for the Galaxy, we estimate masses of the CNMM and the total (disc + halo) WIMM of M CNMM ≲ 8 × 10 8 M⊙ and M WIMM ≃ 8.2 × 10 9 M⊙ .